The Baby Bump - Jones, Kristen P.; King, Eden B.; Gilrane, Veronica L.; McCausland, Tracy C.; Cortina, Jose M.; Grimm, Kevin J. (Journal of Management, 2016)
In light of the prevalent experience, theoretical importance, and underexamination of the intersection of pregnancy and work, the current study explores how pregnant employees manage their concealable stigmatized identities at work over the course of pregnancy. Using a weekly survey methodology, we were able to examine within-person changes in identity management and physical health. Results suggested a reciprocal relationship between revealing and physical health wherein revealing led to more frequent physical health symptoms and more frequent physical health symptoms led to decreased revealing. Furthermore, concealing exerted a unidirectional impact on physical health wherein concealing predicted subsequent decreases in physical health symptoms. Finally, supportive work–family cultures and supervisor support were linked to lower concealing, higher revealing, and less frequent physical health symptoms at the initial measurement occasion (i.e., earlier stages of pregnancy); however, these benefits appeared to diminish over time. The implications of these findings for theory and practice are discussed.